Sistem Manajemen Laboratorium Komputer Berbasis Website - Naufal Rizki, Muhammad; Christanto, Febrian Wahyu; Saufik Suasana, Iman; Ahmad Firdaus, Eryan; Saragih, Hondor; Maulani, Shanti (Jurnal Sistem Informasi Galuh, 2025)
Computer laboratory is an important aspect of supporting the learning process at the Politeknik Kesehatan Kemenkes Semarang. However, manual laboratory management is currently inefficient and prone to errors that can reduce the effectiveness of laboratory use by up to 30% and have a direct impact on the quality of learning. Primary data collected includes laboratory specifications such as the availability of 165 computer units, adequate printers for printing needs, internet networks, and additional tools to support practicums. The laboratory is also supported by technical and admin staff who are responsible for the operation and maintenance of equipment and are equipped with a data management system to help smooth activities. To overcome these management problems, this study implemented a website-based laboratory management system using the Prototype method which is designed to simplify the administration process with centralized management, increase management efficiency, and reduce administrative errors. The system implementation test using the Black Box method obtained 100% functional system results running well. The results of the User Acceptance Testing (UAT) analysis obtained a value of 90.6% which indicates that the developed system can overcome existing problems. Further development is expected to improve the quality of laboratory services and expand the use of information technology in education management at the Politeknik Kesehatan Kemenkes Semarang.